Cloning and Immunological Characterization of Recombinant Vibrio Cholerae O-Antigen Transport Protein Expressed in Lactococcus Lactis - Zamri, Hana Farizah (2011)
The food grade Lactococcus lactis is a potential vehicle for protein delivery via the oral route. This study used lactococcal strains as models for producing the wzm gene that codes for the porin protein involved in transport of Vibrio cholerae lipopolysaccharide O-antigen. The 750 bp gene fragment was PCR-amplified from Vibrio cholerae O1 clinical isolates and cloned into the L. lactis nisin-controlled gene expression vector pNZ8048. The constructs were electrotransformed into L. lactis NZ9000 host strains where transcription of the gene on the RNA level was confirmed by reverse transcriptase PCR. Sequence comparison and multiple alignment of the translated cDNA nucleotides with that of known proteins reveal the presence of conserved structural domains of the ABC-2 membrane superfamily integral membrane protein component. Due to its hydrophobic nature, whole cell L. lactis protein extract was subjected to solubilisation with the detergents sodium dodecyl sulfate (SDS) and Triton X-100 before being separated on SDS-PAGE and analysed on Western blot. In the case of the current study, solubilisation using SDS was found to be more efficient when compared to Triton X-100 in retrieving the expressed ≈ 34 kDa wzm porin as observed upon western blot analysis. ELISA readings showed that oral administration of recombinant L. lactis into New Zealand White rabbits elicited a statistically significant increase of both IgG and IgA levels (P < 0·05) when compared to the control group given only the preparation buffer. Challenge study with virulent V. cholerae O1 strains via the oral route evoked watery diarrhoea in rabbits given only the buffer throughout the immunization period, but fecal passing of both the recombinant and non-recombinant L. lactis groups were normal. This indicates a positive effect of the Lactococcal cells itself, probably towards the intestinal microbiota, in protecting against the adverse effects of V. cholerae and in evading diarrhoea. The diarrhoea lasted approximately two days in the control group, while the others were observed to be diarrhoea-free until the end of the study. Bioinformatics and molecular methods have enabled prediction and detection of the wzm protein product which, as shown in this study, possesses the potential to elicit antibody production and enhance immunity. Administration of the L. lactis bacterium through the oral route was shown to increase mucosal immunity and assist in conferring protection against the diarrhoeal-causing disease cholera. These results provide more insight into the relatively unknown product of V. cholerae wzm, while providing a potential alternative for health improvement against cholera that could be further developed for a safer, convenient, and effective method in protection and prevention of this disease.